Status of the coral formations of Bajo Nuevo Reef Complex, Western Caribbean, Colombia - Gómez Cubillos, Martha Catalina; Daza Guerra, Carlos Andrés; Lozano Mendoza, Nelson Alejandro; Zea, Sven (Revista de Biología Tropical, 2025)
Introduction: Although many reefs have been disturbed by the combined effects of climatic and non-climatic stressors, there still are regions largely free from direct human pressures such as runoff, pollution, and maritime traffic due to their geographic remoteness. This suggests that they are replicas of “pristine reefs”, that allow the investigation of relationships between reef communities and their environment. Objective: To evaluate the status of the coral formations of Bajo Nuevo, Seaflower Biosphere Reserve. Methods: The coral health and the relative cover of reef-building organisms and of their main competitors were evaluated. In every station (11), ten photo quadrants of 0.25 m2 were evaluated along a 10 m tape measure combined, along with ~3 min videos. Results: 32 coral species were recorded, 30 of them Scleractinia and two of hydrocorals, with the highest richness in the reef lagoon. In 2021, the reefs in Bajo Nuevo were dominated by non-reef-building organisms (61.7 ± 0.10 %), the building species represented only 23.9 ± 0.10 %; 3.2 ± 0.03 % was coral skeleton with recent and transitional death less than 15 days old. Signs of diseases affected three genera, 13 species and 23.5 % of the colonies evaluated, of which 84.9 % showed one of the four signs related to the stony coral tissue loss disease. Conclusions: With previous expeditions (2010-2011) as a reference, this reef complex registered in 2021 a drop in the cover of hard corals and calcareous algae, and coral richness; an increase in the cover of non-reef-building organisms, with a high prevalence of signs of unhealthiness associated with different coral diseases. This confirms that these reefs are in danger (EN), as suggested by the red list of marine and coastal ecosystems of Colombia.